HUBUNGAN PENGETAHUAN IBU TENTANG PERKEMBANGAN BALITA USIA 12–36 BULAN DI POSYANDU KUTILANG KELURAHAN SUNGAI MEDANG - Anggriani, Gustika; Widya Astuti, Desti; Septiana, Maria (LPPM STIKes Mitra Adiguna, 2025)
Stimulation is a very important requirement for toddler growth and development. Toddler age children who get a lot of directed stimulation will develop faster than children who get less stimulation. Providing stimulation for children's motor development needs which can be done with education and games that support toddler motor skills. The purpose of this study was to determine the relationship between mother's knowledge about the development of toddlers aged 2-36 months at the Kutilang Posyandu, Sungai Medang Village, This study used an Analytical Survey using a Cross Sectional approach. The population of this study were all mothers who had toddlers 12-36 months at the Kutilang Posyandu, Sungai Medang Village, Prabumulih City in 2021, totaling 43 respondents. The number of samples in this study were 43 respondents. In the univariate analysis, it was found that from 43 respondents, 31 respondents (72.1%) had good knowledge and 12 respondents (27.9) had poor knowledge. Bivariate analysis showed that there was a significant relationship between mother's knowledge about toddler development (p value 0.001). The conclusion of this study is that there is a relationship between mother's knowledge about the development of toddlers aged 2-36 months at the Kutilang posyandu, Sungai Medang Village.